2013
DOI: 10.1097/shk.0b013e318280409a
|View full text |Cite
|
Sign up to set email alerts
|

Tranexamic Acid and Trauma

Abstract: A recent large civilian randomized controlled trial on the use of tranexamic acid (TXA) for trauma reported important survival benefits. Subsequently, successful use of TXA for combat casualties in Afghanistan was also reported. As a result of these promising studies, there has been growing interest in the use of TXA for trauma. Potential adverse effects of TXA have also been reported. A US Department of Defense committee conducted a review and assessment of knowledge gaps and research requirements regarding t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(35 citation statements)
references
References 23 publications
0
35
0
Order By: Relevance
“…Despite this favorable outcome, several gaps in knowledge regarding the use of TXA in trauma were identified in a recent review by a United States Department of Defense Committee. Many issues raised are important in the pediatric population as well, including the need for: (1) a more clear cut identification of which patients might benefit from TXA, (2) development of animal models to establish efficacy and safety, and (3) further evaluation of the safety profile of TXA given the increased risk for thrombotic events and the lack of data regarding safety in children [93]. A 2008 systematic review analyzing the use of TXA in pediatric patients undergoing spine surgery revealed six studies.…”
Section: Treatment Options For Tic In Pediatric Traumamentioning
confidence: 99%
“…Despite this favorable outcome, several gaps in knowledge regarding the use of TXA in trauma were identified in a recent review by a United States Department of Defense Committee. Many issues raised are important in the pediatric population as well, including the need for: (1) a more clear cut identification of which patients might benefit from TXA, (2) development of animal models to establish efficacy and safety, and (3) further evaluation of the safety profile of TXA given the increased risk for thrombotic events and the lack of data regarding safety in children [93]. A 2008 systematic review analyzing the use of TXA in pediatric patients undergoing spine surgery revealed six studies.…”
Section: Treatment Options For Tic In Pediatric Traumamentioning
confidence: 99%
“…6,7 The use of TXA in adult trauma is based on the results of a large, multicenter, randomized placebo controlled trial (The CRASH-2 (Clinical Randomisation of an Antifibrinolytic in Significant Hemorrhage 2), which demonstrated that early administration of TXA could improve survival in trauma patients. This was potentially explained by the adequate inhibition of fibrinolytic activity obtained after the administration of 2 g TXA over 8 hours.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, one may argue that tranexamic acid should have been administered to our patients anyhow. Although debated the Cochrane review from 2012 suggests that tranexamic acid safely reduces mortality in bleeding trauma patients without increasing the risk of adverse events [12, 13]. There is of course a need for further data before any general recommendation for the use of tranexamic acid as part of the management of suspected TRALI.…”
Section: Discussionmentioning
confidence: 99%